Problem-Focused Coping pada Mahasiswa Aktif Fakultas Pendidikan dan Bahasa Universitas Katolik Indonesia Atma Jaya Jakarta - Laurentia Chezary Tito Pitaloka; Henny Christine Mamahit (Universitas Kanjuruhan Malang, 2021)
Problem-focused coping is a strategy to reduce academic stress situations by doing something constructive to be free from stressful situations. Coping focused on problems; there are five dimensions: active coping, planning, suppressing competing activities, delaying stress coping, and seeking social support for help (seeking social support for instrumental reasons). The purpose of this study was to describe the use of problem-focused coping inactive students of the Faculty of Education and Language (FPB) class 2016-2019 at the Atma Jaya Catholic University of Indonesia, Jakarta. This research is descriptive quantitative research. The trial sample in this study was 70 students, and the research sample consisted of 152 students. Data were collected using a problem-focused coping questionnaire in the form of a rating scale. Of the 40 statements compiled, there are 38 valid with reliability of 0.935. Based on the calculation of the description of using coping focused on student problems class 2016-2019, FPB is included in the high classification/category, which is 54.6%. The active coping component is coping behavior which ranks first with a total of 623. In other words, students use operational activities and strive for positive actions to reduce academic stress.